Characterization of spatial coherence of synchrotron radiation with non‐redundant arrays of apertures. (12th May 2014) - Skopintsev, P.; Singer, A.; Bach, J.; Müller, L.; Beyersdorff, B.; Schleitzer, S.; Gorobtsov, O.; Shabalin, A.; Kurta, R. P.; Dzhigaev, D.; Yefanov, O. M.; Glaser, L.; et al.
<x xml:space="preserve">Abstract</x> A method to characterize the spatial coherence of soft X‐ray radiation from a single diffraction pattern is presented. The technique is based on scattering from non‐redundant arrays (NRAs) of slits and records the degree of spatial coherence at several relative separations from 1 to 15 µm, simultaneously. Using NRAs the spatial coherence of the X‐ray beam at the XUV X‐ray beamline P04 of the PETRA III synchrotron storage ring was measured as a function of different beam parameters. To verify the results obtained with the NRAs, additional Young's double‐pinhole experiments were conducted and showed good agreement.